Reactive lymphoid hyperplasia mimicking acute appendicitis in children: a retrospective analysis of 259 cases - Neslihan Gulcin; M. Sddk Dicle; Cengiz Gul; Semih L. Mirapoglu; Ceyhan Sahin; Mehmet Arpack; Aytekin Kaymakc (BMC Pediatrics)
Abstract Purpose This study aimed to evaluate and compare the clinical, laboratory, imaging, and histopathological findings of pediatric patients diagnosed with reactive lymphoid hyperplasia (RLH) among those who underwent surgery with a pre-diagnosis of acute appendicitis. Methods A retrospective analysis was conducted on 3,469 pediatric patients who underwent appendectomy between January 2013 and January 2025. A total of 259 patients with histopathologically confirmed RLH were included in the study. Their clinical presentations, laboratory parameters, imaging findings, and surgical notes were analyzed. Where possible, comparisons were made with the remaining cohort. Results Among the RLH cases, 61% were male, with a mean age of 11.6 ± 4.2 years. Inflammatory markers such as WBC and CRP were elevated in only a subset of patients. Although ultrasonographic findings frequently mimicked acute appendicitis, histopathological evaluation revealed no signs of true inflammation. Laparoscopic appendectomy was performed in 77.2% of RLH patients, and all were discharged without complications. During follow-up, some patients developed systemic or autoinflammatory conditions such as FMF, IBD, or celiac disease. Comparative analysis showed that such conditions were significantly more common in the RLH group than in the non-RLH cohort. Conclusions RLH is a benign condition that may clinically and radiologically mimic acute appendicitis. In stable pediatric patients with low inflammatory markers, conservative management should be considered to avoid unnecessary surgical interventions. Preoperative identification remains challenging, highlighting the importance of a multidisciplinary diagnostic approach. This study, with one of the largest cohorts to date, provides new insights into the natural history and diagnostic pitfalls of RLH. Clinical trial registration Clinical trial number: Not applicable.